The Effect of Massage on Delayed Onset Muscle Soreness of Sedentaries - Sözen, H.; Tekat, A. (My University, 2008)
The present study was designed to observe the effect of massage on delayed onset muscle soreness of sedentaries. A total of 26 healthy sedanter male university students aged between 18 and 25 voluntereed to participate the study. All participants were student at Ondokuz Mayis University in Samsun, Turkey. Participants placed into two groups, massage and control groups and there were 13 students in each group. Five sets of 10 maximal exercises in the eccentric mode were applied to the hamstrings of the right leg to induce delayed onset muscle soreness in all volunteers. The Leg Curl machine was used for these exercises. The subjects in the massage group receive a-twenty .minrte classical (Swedish) massage two hours after the exercise, Massage was administered to the hamstrings (muscles) Of the right legs of those in the massage group. A blood sample were taken from all subjects to measure serum creatine enzyme (CK), before the workout, and six, twenty-four and forty-eight hours after the workout. Statistical Package for Social Sciences (SPSS) was used to analyze the data. Independent sample t-test was performed to compare the effects of massage on serum creatine enzyme (CK) level for both groups. Although massage given two hours after workout has somewhat effect on creatine kinase levels measured between 6 to 10 hours following workout, this effect was not found statistically significant. However difference in creatine kinase levels after 48 hours was found significant (t(24) = -2.552; p <0.05). This result has shown that massage can cause a decrease in creatine kinase levels and that the effect of the massage administered 2 hours after workout peaks at only 48 hours after workout.
Keywords: Massage; Soreness